2020
DOI: 10.1186/s13287-020-01911-4
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-based Smad7 gene therapy for experimental liver cirrhosis

Abstract: Background Bone mesenchymal stem cells (MSCs) can promote liver regeneration and inhibit inflammation and hepatic fibrosis. MSCs also can serve as a vehicle for gene therapy. Smad7 is an essential negative regulatory gene in the TGF-β1/Smad signalling pathway. Activation of TGF-β1/Smad signalling accelerates liver inflammation and fibrosis; we therefore hypothesized that MSCs overexpressing the Smad7 gene might be a new cell therapy approach for treating liver fibrosis via the inhibition of TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…MSCs participate in the regulation of TGF-β downstream pathways. MSCs were able to significantly down-regulate the mRNA expression of TGF-β1 and TGFBR1 downstream molecule SMAD3 and increase the mRNA expression of SMAD7 ( 71 ). It has been demonstrated that SMAD3 upregulates the expression of the pro-fibrotic factor α-SMA or Col1a1, whereas SMAD7 has an anti-fibrotic impact.…”
Section: Mesenchymal Stem Cell Therapies For Liver Cirrhosis: Immune ...mentioning
confidence: 99%
“…MSCs participate in the regulation of TGF-β downstream pathways. MSCs were able to significantly down-regulate the mRNA expression of TGF-β1 and TGFBR1 downstream molecule SMAD3 and increase the mRNA expression of SMAD7 ( 71 ). It has been demonstrated that SMAD3 upregulates the expression of the pro-fibrotic factor α-SMA or Col1a1, whereas SMAD7 has an anti-fibrotic impact.…”
Section: Mesenchymal Stem Cell Therapies For Liver Cirrhosis: Immune ...mentioning
confidence: 99%
“…BMSC overexpressing Smad7 significantly reduced plasma levels of laminin and hyaluronic acid, components of the ECM. Furthermore, Smad7-MSC mediated an increase in serum expression of MMP-1 and a decrease in TIMP-1 [ 131 ]. MMP is a class of matrix-degrading proteases that mainly degrade scarring in the subendothelial space.…”
Section: Mechanisms Of Stem Cell Therapy For Liver Fibrosismentioning
confidence: 99%
“…Inflammatory cytokines induce the transdifferentiation of HSCs from a quiescent to a proliferative, migratory, and fibrotic phenotype (myofibroblast). This leads to the generation of plenty of extracellular matrix (ECM) as well as the expression of α-smooth muscle actin (α-SMA) [21]. TGF-β is the main cytokine in the stimulation of HSCs trans-differentiation and the signal of epithelial-to-mesenchymal transitions (EMT).…”
Section: Pathogenesis Of Liver Cirrhosismentioning
confidence: 99%